A Model for Estimating Coral Species Richness of Indonesian Coral Reefs - Bahtiar, Imam; Budiyanto, Agus (Journal of Indonesian Coral Reefs, 2011)
Marine biodiversity at species level is crucially important ini ecologicalÂ  assessment and aceosystem management. Data on coral richness, however, are very race for many reefs in Indonesia, due to low number of available coral taxonomist in many provinces and districts. The objective of present sudy was to find a regression model for estimating species richness of Scleractinian corals, based on line-intercept-transect data. Wakatobi and Pangkep (Pangkajenne Kepulauan). The result showed that coral species richness can be estimated from three predictor variables: coral acroporiid covers (CAC), coral masive and submassive cover (CMS), and number of coral genera(CGR). Develop multiple regression model showed considerably high cooficient of determination (73.55%) in estimating coral species richness. Model validation using data from coral reefs on Lembaga waters showed that the model worked well, i.e. estimated and in situ recordered species richness are strongly correlated.